Strategi Pemasaran Pendidikan MI Nurul Huda 2 Kota Mojokerto - Nurdiana, Defi Dachlian (AKSI: Jurnal Manajemen Pendidikan Islam, 2024)
Marketing strategy is a series of important activities that must be carried out in the marketing process, especially the marketing of educational institutions that sell educational services. Marketing that is right on target and effective is able to influence consumers to be interested in buying and using educational services. The purpose of this study was to determine the educational marketing strategy of MI Nurul Huda 2 Mojokerto City. This research uses qualitative methods, purposive sampling techniques, data collection techniques Observation, Interview, and Documentation. Data analysis using the Milles and Huberman method, source triangulation data validity. The results of the study focus on extracurricular development by utilising marketing communication through seven mixes including advertising, promotions, events and experiences, news, public relations, sales promotion, public relations, personal selling, direct marketing. To maintain consumer purchasing power, prioritise trust and improve educational services.